Antioxidant Activities and Cytotoxicity Screening of the Extracts from Indigo (Indigofera tinctoria) - Poonkasem, Yada; Damrianant, Somchit; Sakkayawong, Niramol (Thai Journal of Science and Technology, 2022)
Antioxidant activities and cytotoxicity screening of the ethanol extracts from different parts of Indigo (Indigofera tinctoria) including mature leaves, immature leaves and seeds, were investigated. All samples were prepared by Soxhlet extractions with absolute ethanol. Total phenolic content (TPC) by Folin-Ciocalteu method and radical scavenging analyses by DPPH (1,1 diphenyl-2-picrylhydrazyl) and FRAP (ferric reducing antioxidant power) were employed. The levels of TPC were high in the crude extracts from mature and immature leaves, 12.34±2.59 and 12.90±3.13 mg GAE/g dried weight, respectively, while antioxidant activity by FRAP was increased in that from the seeds, 135.21±15.16 µmol/g dried weight. The IC50 (half maximal inhibitory concentration) values by DPPH were low in the seed extracts, 0.23±0.10 mg/mL. The major compounds in the extracts were further identified by thin layer chromatography (TLC). The leaf extracts were displayed to contain rutin, quercetin, kaempferol, and apigenin. In addition, epicatachin and gallic acid were unveiled in the seed extracts. Cytotoxic assays to human dermal fibroblasts-adult (HDFa) shown by ED50 (half maximal effective dose) values, in the extracts from mature leaves, immature leaves and seeds were 1.14 x 103, 1.55 x 103 and 4.26 x 103 mg/mL, respectively. It is suggested that the ethanol extracts from Indigo possess a valuable aspect to be developed as a potential phytomedicine.